A proteomic approach to understand MMP‐3‐driven developmental processes in the postnatal cerebellum: Chaperonin CCT6A and MAP kinase as contributing factors. Issue 9 (18th February 2015) - Van Hove, Inge; Verslegers, Mieke; Hu, Tjing‐Tjing; Carden, Martin; Arckens, Lutgarde; Moons, Lieve
ABSTRACT Matrix metalloproteinase‐3 (MMP‐3) deficiency in mice was previously reported to result in a transiently retarded granule cell migration at postnatal day 8 (P8) and a sustained disturbed arborization of Purkinje cell dendrites from P8 on, concomitant with a delayed synapse formation between granule cells and Purkinje cells and resulting in mild deficits in motor performance in adult animals. However, the molecular mechanisms by which MMP‐3 contributes to proper development of the cerebellar cortex during the first postnatal weeks remains unknown. In this study, we used a functional proteomics approach to investigate alterations in protein expression in postnatal cerebella of wild‐type versus MMP‐3 deficient mice, and to further elucidate MMP‐3‐dependent pathways and downstream targets in vivo. At P8, two‐dimensional difference gel electrophoresis and mass spectrometry identified 20 unique proteins with a different expression between the two genotypes. Subsequent "Ingenuity Pathway Analysis" and Western blotting indicate that the chaperonin containing T‐complex polypeptide 1, subunit 6A and the MAP kinase signaling pathway play a key role in the MMP‐3‐dependent regulation of neurite outgrowth and neuronal migration in the developing brain. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 75: 1033–1048, 2015